1996
DOI: 10.1007/s002800050539
|View full text |Cite
|
Sign up to set email alerts
|

Electropermeabilization in bladder cancer chemotherapy

Abstract: The electropermeabilization technique has the potential to serve as a new and effective modality for the treatment of bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…4,24,25 Nevertheless, any increase in the CIS or MMC cytotoxicity is appreciated because bladder cancer is already sensitive to these drugs. Our study shows that electrochemotherapy was effective using intratumor MMC or CIS.…”
Section: Discussionmentioning
confidence: 99%
“…4,24,25 Nevertheless, any increase in the CIS or MMC cytotoxicity is appreciated because bladder cancer is already sensitive to these drugs. Our study shows that electrochemotherapy was effective using intratumor MMC or CIS.…”
Section: Discussionmentioning
confidence: 99%
“…KK-47, a low-grade and non-metastatic bladder tumor cell line (11), was generously provided by Dr T. Masuko, Tohoku University (Sendai, Japan) and YTS-1, a high-grade and metastatic bladder tumor cell line (12) was a generous gift from Dr H. Kakizaki, Yamagata University (Yamagata, Japan). Cells were maintained in RPMI-1640 medium (Sigma-Aldrich, St. Louis, MO, USA) supplemented with 10% fetal bovine serum (FBS) (PAA Laboratories, Morningside, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, this method enables the introduction of any non-permeant or weakly permeant molecules into cells [9]. Recently, this method has been used to enhance the cytotoxicity of antineoplastic drugs [10, 11, 12], and we have already shown that such enhancement is caused by the increased uptake of drugs by cells [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Such electric fields have been used to facilitate the introduction of cytotoxic drugs or genes into cells [5, 6]. We have already shown that electropermeabilization induces a twofold increase in the concentration of bleomycin (BLM) in bladder cancer cells in vitro and in normal bladder tissues of rats in vivo [7]. The aim of the present investigation was to examine the possible enhancement of the antitumor effect of BLM by electropermeabilization in rats with bladder cancer.…”
Section: Introductionmentioning
confidence: 99%